Pemberian Kompensasi Strategi dan Implikasi dalam Konteks Organisasi Modern - Santoso, Imam Sugeng; Aisyah, Euis Tatu; Kurniawan, Muhamad Ade; Destriyanti, Rini Ayu (Journal of Industrial and Engineering System, 2023)
In the pursuit of business activities, companies require various resources such as capital, materials, machinery, and notably, human resources represented by employees. Employees, possessing talents, energy, and creativity, play a crucial role in achieving the company's objectives. This reciprocal relationship is driven by the employees' needs, motivating them to work. In this research, one shot time horizon is used with cross-section data type. Descriptive hypothesis testing using the technique of determining the average score. In verification research, the modeling approach and solution technique that will be used as an analysis tool is the variant or component-based structural equation modeling (SEM) method, namely PLS (partial least square). The results include that competitive salaries are an important component of an effective compensation strategy. Attractive perks and benefits can help organizations attract and retain the best employees. An objective and transparent performance appraisal system can help to ensure that high-performing employees receive appropriate compensation.